A automobilização de uma teleatendente para enfrentar as adversidades do trabalho em um Call Center - Marcello Santos Rezende; Jussara Brito; Milton Athayde (Universidade do Porto, 2009)
The aim of this explorative study was to understand the activities of operators in a large telemarketing call center and the relationship of this work to their health. The general theoretical references used were the concepts of life and health as seen in the work of Canguilhem and the ergological perspective, incorporating theoretical and methodological tools of clinical approaches to work, such as the Psychodynamics of Work and the Clinic of the Activity. The "interview" conducted was inspired by the technique of "instructions to the double". It was noted that the most adverse situation faced by telemarketers at work is that related to the establishing of an average service time which must be met regardless of the type of client and situation. However, we realize that without the use that workers make of their time, the script, their verbal expressions and relationships with other workers, the work activity at the call center would be even more destructive and they would hardly ever reach the expected results.